Answer:
D) y = x - 1
Explanation:
First we need the general equation of point slope form:
(y - y0) = m(x - x0)
Where y0 is the y coordinate and x0 is the x coordinate and m is the slope.
For the line to be perpendicular, we need the slope to be the negated opposite of the other equation. So the negated opposite of -1 is 1.
So our m = 1, y0 = -2, and x0 = -1. Now let's plug this into the equation and reform the equation into slope-intercept form
(y - (-2)) = 1 (x - (-1))
y + 2 = 1 (x + 1)
y + 2 = x + 1
y = x - 1
So the equation of the line that goes through the point (-1,-2) and is perpendicular to the line y = -x -1, is y = x - 1.
Cheers.